Assessing the impact of transitional care units on dialysis patient outcomes: A multicenter, propensity score‐matched analysis. Issue 2 (9th February 2023) - Blankenship, Derek M.; Usvyat, Len; Kraus, Michael A.; Chatoth, Dinesh K.; Lasky, Rachel; Turk, Joseph E.; Maddux, Franklin W.
Abstract: Introduction: Inadequate predialysis care and education impacts the selection of a dialysis modality and is associated with adverse clinical outcomes. Transitional care units (TCUs) aim to meet the unmet educational needs of incident dialysis patients, but their impact beyond increasing home dialysis utilization has been incompletely characterized. Methods: This retrospective study included adults initiating in‐center hemodialysis at a TCU, matched to controls (1:4) with no TCU history initiating in‐center hemodialysis. Patients were followed for up to 14 months. TCUs are dedicated spaces where staff provide personalized education and as‐needed adjustments to dialysis prescriptions. For many patients, therapy was initiated with four to five weekly dialysis sessions, with at least some sessions delivered by home dialysis machines. Outcomes included survival, first hospitalization, transplant waiting‐list status, post‐TCU dialysis modality, and vascular access type. Findings: The study included 724 patients initiating dialysis across 48 TCUs, with 2892 well‐matched controls. At the end of 14 months, patients initiating dialysis in a TCU were significantly more likely to be referred and/or wait‐listed for a kidney transplant than controls (57% vs. 42%; p < 0.0001). Initiation of dialysis at a TCU was also associated with significantly lower rates of receiving in‐center hemodialysis at 14 months (74% vs. 90%; p < 0.0001) and higher rates of arteriovenous access (70% vs. 63%; p = 0.003). Although not statistically significant, TCU patients were more likely to survive and less likely to be hospitalized during follow‐up than controls. Discussion: Although TCUs are sometimes viewed as only a means for enhancing utilization of home dialysis, patients attending TCUs exhibited more favorable outcomes across all endpoints. In addition to being 2.5‐fold more likely to receive home dialysis, TCU patients were 42% more likely to be referred for transplantation. Our results support expanding utilization of TCUs for patients with inadequate predialysis support.